Numerical Evaluation of the Vibration Reduction Index for Structural Joints - RAMIS, Jaime; SEGOVIA, Enrique; ALBA, Jesus; CARBAJO, Jesus; GODINHO, Luıs (Archives of Acoustics, 2013)
The present paper addresses the analysis of structural vibration transmission in the presence of struc- tural joints. The problem is tackled from a numerical point of view, analyzing some scenarios by using finite element models. The numerical results obtained making use of this process are then compared with those evaluated using the EN 12354 standard vibration reduction index concept. It is shown that, even for the simplest cases, the behavior of a structural joint is complex and evidences the frequency dependence. Comparison with results obtained by empirical formulas reveals that those of the standards cannot accurately reproduce the expected behavior, and thus indicate that alternative complementary calculation procedures are required. A simple methodology to estimate the difference between numerical and standard predictions is here proposed allowing the calculation of an adaptation term that makes both approaches converge. This term was found to be solution-dependent, and thus should be evaluated for each structure.